Aqueous dispersion, method for producing aqueous dispersion, and method for producing composite material

The use of a specific aqueous dispersion with tailored PTFE and heat-melting fluororesin particles A and B forms a composite material with superior adhesion and flexibility, addressing the limitations of existing PTFE-based materials.

JP2025006647APending Publication Date: 2025-01-17AGC INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023107567
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing composite materials made from PTFE dispersions lack sufficient adhesion and flexibility, requiring improvements in adhesiveness, bendability, and impregnation properties.

Method used

An aqueous dispersion containing polytetrafluoroethylene (PTFE) particles, heat-melting fluororesin particles A, and heat-melting fluororesin particles B with a carbonyl group-containing group, where the average particle diameter of particles A is between those of PTFE and B, with a mass content of A greater than B, and the total mass of A and B is less than PTFE, is used. This dispersion is applied to a fiber base material and heated multiple times to form a composite material.

Benefits of technology

The resulting composite material exhibits enhanced adhesion, bendability, and impregnation properties, with PTFE particles remaining intact even under stress, demonstrating improved adhesiveness and flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006647000001
    Figure 2025006647000001
Patent Text Reader

Abstract

To provide an aqueous dispersion which enables provision of a composite material excellent in adhesion and bending property and is also excellent in impregnation property, a method for producing an aqueous dispersion, and a method for producing a composite material.SOLUTION: An aqueous dispersion contains polytetrafluoroethylene particles, heat-fusible fluororesin particles A, and heat-fusible fluororesin particles B having a carbonyl group-containing group, wherein an average particle diameter (D50) of the heat-fusible fluororesin particles A is equal to or more than an average particle diameter (D50) of the polytetrafluoroethylene particles, and is smaller than an average particle diameter (D50) of the heat-fusible fluororesin particles B having the carbonyl group-containing group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to aqueous dispersions, methods for making aqueous dispersions, and methods for making composite materials. [Background technology]

[0002] Polytetrafluoroethylene (hereinafter, also referred to as "PTFE") has excellent physical properties such as mold releasability, electrical properties, water and oil repellency, chemical resistance, weather resistance, and heat resistance, and is used for various industrial applications by utilizing these physical properties. For example, it is known that a heat-resistant tape can be obtained by impregnating a glass fiber fabric with a PTFE emulsion, sintering the fabric, and then surface-treating the fabric with a solution containing perfluoroalkoxyalkane (hereinafter, also referred to as "PFA") (see Patent Document 1). It is also known that a molded product with excellent adhesion can be obtained by applying a dispersion liquid containing a powder of a copolymer containing tetrafluoroethylene (hereinafter, also referred to as "TFE") units, 5-norbornene-2,3-dicarboxylic anhydride (hereinafter, also referred to as "NAH") units, and perfluoro(propyl vinyl ether) (hereinafter, also referred to as "PPVE") units, and a powder of PTFE to a copper foil and baking the resulting product (see Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2020-513437 [Patent Document 2] International Publication No. 2020 / 004339 Summary of the Invention [Problem to be solved by the invention]

[0004] As described above, it is known to obtain a composite material using a dispersion of PTFE, etc. However, the composite material is required to have further adhesiveness and processing properties, particularly flexibility.

[0005] The present disclosure has been made in consideration of the above, and aims to provide an aqueous dispersion that can give a composite material having excellent adhesion and bendability and also has excellent impregnation properties, a method for producing the aqueous dispersion, and a method for producing a composite material. [Means for solving the problem]

[0006] Specific means for solving the above problems include the following aspects. <1> An aqueous dispersion comprising polytetrafluoroethylene particles, heat-meltable fluororesin particles A, and heat-meltable fluororesin particles B having carbonyl group-containing groups, wherein the average particle size (D50) of the heat-meltable fluororesin particles A is equal to or larger than the average particle size (D50) of the polytetrafluoroethylene particles and is smaller than the average particle size (D50) of the heat-meltable fluororesin particles B having carbonyl group-containing groups. <2> The content by mass of the heat-meltable fluororesin particles A is equal to or greater than the content by mass of the heat-meltable fluororesin particles B having a carbonyl group-containing group, <1> The aqueous dispersion according to claim 1. <3> the total mass of the heat-meltable fluororesin particles A and the heat-meltable fluororesin particles B having a carbonyl group-containing group is less than the mass of the polytetrafluoroethylene particles; <1> or <2> The aqueous dispersion according to claim 1. <4> the content by mass of the carbonyl group-containing group-containing heat-meltable fluororesin particles B is less than the content by mass of the polytetrafluoroethylene particles and less than the content by mass of the heat-meltable fluororesin particles A; <1> ~ <3> 13. The aqueous dispersion according to claim 12, <5> The melt processable fluororesin particles A are particles of a resin containing a unit based on tetrafluoroethylene and at least one of a unit based on perfluoro(alkyl vinyl ether) and a unit based on hexafluoropropylene. <1> ~ <4> 13. The aqueous dispersion according to claim 12, <6> The carbonyl group-containing group is an acid anhydride residue. <1> ~ <5> 13. The aqueous dispersion according to claim 12, <7> an aqueous dispersion of heat-meltable fluororesin particles A and heat-meltable fluororesin particles B having a carbonyl group-containing group are mixed and sheared to obtain a sheared liquid, and the sheared liquid is mixed with an aqueous dispersion of polytetrafluoroethylene particles; <1> ~ <6> 13. A method for producing the aqueous dispersion according to claim 12. <8> On the surface of the fiber substrate <1> ~ <6> 1. A method for producing a composite material, comprising the steps of applying the aqueous dispersion according to any one of 1 to 10 and heating the mixture at least twice. <9> the content by mass of the heat-meltable fluororesin particles A in the aqueous dispersion used in the first operation is greater than the content by mass of the heat-meltable fluororesin particles A in the aqueous dispersion used in the operations other than the first operation; <8> A method for producing the composite material according to claim 1. <10> applying an aqueous dispersion of polytetrafluoroethylene particles to the surface of the fiber substrate that has been subjected to the above-mentioned operation, and heating the surface; <8> or <9> A method for producing the composite material according to claim 1. Effect of the Invention

[0007] According to the present disclosure, there are provided an aqueous dispersion which can provide a composite material having excellent adhesion and bendability and which is also excellent in impregnation properties, a method for producing the aqueous dispersion, and a method for producing a composite material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] An embodiment of the present disclosure will be described in detail below. However, the present disclosure is not limited to the following embodiment. In the following embodiment, the components (including element steps, etc.) are not essential unless otherwise specified. The same applies to the numerical values ​​and their ranges, and the present disclosure is not limited thereto.

[0009] In the present disclosure, a numerical range indicated using "~" includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, each component may contain multiple types of the corresponding substance. When multiple substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, multiple types of particles corresponding to each component may be included. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified. In the present disclosure, the "average particle size (D50)" is the volume-based cumulative 50% diameter of particles determined by a laser diffraction / scattering method. In other words, the particle size distribution is measured by a laser diffraction / scattering method, a cumulative curve is calculated with the total volume of the particle group as 100%, and the particle size is the point on the cumulative curve where the cumulative volume is 50%. The average particle size (D50) of particles is determined by dispersing the particles in water and analyzing them by a laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). In the present disclosure, the "melting temperature" is the temperature corresponding to the maximum value of the melting peak of a resin measured by differential scanning calorimetry (DSC). In the present disclosure, the term "melt flow rate" refers to the melt flow rate (MFR) of a resin as defined in JIS K 7210:1999 (ISO 1133:1997). In the present disclosure, the "glass transition temperature (Tg)" is a value measured by analyzing a resin using a dynamic mechanical analysis (DMA) method. In the present disclosure, the "viscosity" is determined by measuring the dispersion using a Brookfield viscometer at 25° C. and a rotation speed of 30 rpm. The measurement is repeated three times, and the average value of the three measured values ​​is used. In the present disclosure, the "thixotropy ratio" is a value calculated by dividing the viscosity η1 of the dispersion measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement is repeated three times, and the average value of the three measured values ​​is used. In the present disclosure, a "resin" is a compound formed by polymerizing a monomer, i.e., a "resin" has a plurality of units based on the monomer. In the present disclosure, the term "unit" in a resin means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by treating the resin.

[0010] ≪Aqueous dispersion≫ The aqueous dispersion of the present disclosure contains polytetrafluoroethylene particles, heat-meltable fluororesin particles A, and heat-meltable fluororesin particles B having carbonyl group-containing groups, and the average particle size (D50) of the heat-meltable fluororesin particles A is equal to or larger than the average particle size (D50) of the polytetrafluoroethylene particles and is smaller than the average particle size (D50) of the heat-meltable fluororesin particles B having carbonyl group-containing groups.

[0011] According to the aqueous dispersion of the present disclosure, a composite material having excellent adhesiveness and bendability can be obtained, and the impregnation of the fiber substrate is also excellent. The action of the aqueous dispersion of the present disclosure is presumed to be as follows. In the aqueous dispersion of the present disclosure, the average particle size of the heat-meltable fluororesin particles A (hereinafter also referred to as "particle A") is equal to or larger than the average particle size of the polytetrafluoroethylene particles (hereinafter also referred to as "PTFE particles") and is smaller than the average particle size of the heat-meltable fluororesin particles B (hereinafter also referred to as "particle B") having a carbonyl group-containing group. In this case, the particles A act as a balancer to promote the interaction between the PTFE particles and the particles B, and the effect of improving the dispersion properties such as the in-liquid dispersibility of the particles B is easily spread to the whole particle. In the aqueous dispersion of the present disclosure in which each particle is uniformly and stably dispersed, the resin of the particles A and B is a heat-meltable resin, so that the flexibility of the resin is easily improved in the composite material formed therefrom. Therefore, such a composite material is a composite material having excellent foldability and PTFE properties (i.e., fibrous surface properties and sliding properties, etc.) that does not show a significant change in the appearance of the fold part even when it is folded under a load. The resin of particle B forms a dense matrix due to the carbonyl-containing groups contained in the resin, and the polymer chains of particle B and PTFE particles are easily entangled with each other. That is, the polymer chains of particle B applied to the fiber substrate are used as the starting point to promote the support of the polymer chains of the PTFE particles. Therefore, in the composite material formed from the aqueous dispersion containing particle A and particle B, even if the surface is rubbed, the PTFE is not easily peeled off from the composite material, and the composite material has higher adhesiveness and PTFE properties. In other words, the composite material formed from the aqueous dispersion of the present disclosure is a composite material with excellent bendability, fibrous surface properties, PTFE physical properties such as sliding properties, and excellent adhesiveness. In this case, it is preferable that the particle B is arranged on the surface side of the fiber substrate so that the PTFE does not peel off from the composite material even when the surface of the composite material is rubbed. Therefore, the average particle diameter of the particle B is made larger than that of the PTFE particles. On the other hand, the particle B having a larger average particle diameter than the PTFE particles is likely to accumulate on the surface side of the fiber substrate and is difficult to penetrate into the fiber substrate. Therefore, the particle A having a smaller average particle diameter than the particle B is contained. It is presumed that this makes it easier to form a structure in which the PTFE does not peel off from the composite material more effectively. In this way, the aqueous dispersion of the present disclosure also has improved impregnation of the fiber substrate. In other words, the aqueous dispersion of the present disclosure has excellent impregnation of the fiber substrate. It should be noted that the present disclosure is in no way limited to the above presumed mechanism.

[0012] <Polytetrafluoroethylene particles> The aqueous dispersions of the present disclosure contain polytetrafluoroethylene particles (ie, PTFE particles). The PTFE particles may be used alone or in combination of two or more kinds. PTFE may be a homopolymer of tetrafluoroethylene (hereinafter also referred to as "TFE"), or may be a so-called modified PTFE, which is a copolymer of TFE and a small amount of comonomer. Examples of the small amount of comonomer include perfluoro(alkyl vinyl ether) (hereinafter also referred to as "PAVE"), hexafluoropropylene (hereinafter also referred to as "HFP"), and fluoroalkylethylene. The proportion of the TFE-based units in the modified PTFE is preferably 99.5 mol % or more, and more preferably 99.9 mol % or more, of all units. The PTFE particles preferably contain PTFE as a main component, and the content thereof is preferably 100% by mass. In addition, PTFE is preferably non-thermofusible. The term "non-thermofusible" means that it is not melt moldable, that is, it does not exhibit melt flowability. Specifically, this means that the melt flow rate measured in accordance with ASTM D3307 at a measurement temperature of 372°C and a load of 49N is less than 0.5g / 10min.

[0013] From the viewpoints of impregnation and handling, the average particle size of the PTFE particles is preferably 0.1 μm or more, more preferably 0.2 μm or more. The average particle size of the PTFE particles is preferably 3 μm or less, more preferably 1 μm or less, even more preferably 0.5 μm or less, and particularly preferably 0.4 μm or less.

[0014] From the viewpoints of impregnation and heat resistance, the content of the PTFE particles relative to the total mass of the aqueous dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more. The content of the PTFE particles relative to the total mass of the aqueous dispersion is preferably 70% by mass or less, more preferably 65% ​​by mass or less, and even more preferably 60% by mass or less.

[0015] The content of the PTFE particles relative to the total mass of the PTFE particles, particles A, and particles B is preferably 50% by mass or more, and more preferably 60% by mass or more. The content of the PTFE particles relative to the total mass of the PTFE particles, particles A, and particles B is preferably 95% by mass or less, and more preferably 90% by mass or less.

[0016] The PTFE particles may be commercially available, or an aqueous dispersion of PTFE particles may be used.

[0017] <Heat meltable fluororesin particles A> The aqueous dispersion of the present disclosure contains heat-meltable fluororesin particles A (that is, particles A). In the present disclosure, the "melt processible fluororesin particle A" does not include the above-mentioned "PTFE particle". In the present disclosure, the "melt processible fluororesin particle A" does not include the below-mentioned "melt processible fluororesin particle B having a carbonyl group-containing group (i.e., particle B)". In the present disclosure, the term "thermal meltability" refers to the property that there exists a temperature at which the melt flow rate is 1 to 1000 g / 10 min under a load of 49 N. The number of carbonyl group-containing groups contained in the resin of particle A is smaller than the number of carbonyl group-containing groups contained in the resin of particle B described below, and is usually 1×10 6Preferably, the number of carbonyl-containing groups per unit is less than 100. In the present disclosure, the number of carbonyl-containing groups in the resin can be quantified by the composition of the resin or the method described in WO 2020 / 145133.

[0018] From the viewpoints of adhesion, bendability and impregnation, the particles A are preferably particles of a resin containing a unit based on tetrafluoroethylene (TFE) and at least one of a unit based on perfluoro(alkyl vinyl ether) (PAVE) and a unit based on hexafluoropropylene (HFP). From the viewpoints of adhesion, bendability and impregnation, the particles A are more preferably particles of a resin (PFA) containing a unit based on TFE and a unit based on PAVE, or particles of a resin (FEP) containing a unit based on TFE and a unit based on HFP. From the viewpoints of adhesion, bendability and impregnation, the particles A are more preferably perfluoroalkoxyalkane (PFA) particles or tetrafluoroethylene-hexafluoropropylene copolymer (FEP) particles. As the PAVE, CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE") are preferred, and PPVE is more preferred.

[0019] The composition ratio of each monomer unit in the resin of particle A is not particularly limited, but for example, when the resin contains a unit based on TFE, the composition ratio of the unit based on TFE is preferably 70 to 99 mol% relative to the total units in the resin from the viewpoint of favorably expressing the characteristics due to TFE.Furthermore, for example, when the resin contains a unit based on PAVE or a unit based on HFP, the composition ratio of the unit based on PAVE or the unit based on HFP is preferably 1 to 5 mol% relative to the total units in the resin, and 20 to 30 mol% relative to the total units in the resin from the viewpoint of favorably expressing the characteristics due to PAVE or HFP. The fluorine content of the resin of particles A is preferably 70 to 76 mass %, since interaction with PTFE is likely to occur, peeling of PTFE from the composite material can be further suppressed, and the heat resistance of the composite material can be further improved.

[0020] When the resin of the particles A is PFA or FEP, the particles A preferably contain PFA or FEP as a main component, respectively, and the content of PFA or FEP is preferably 100% by mass.

[0021] From the viewpoints of impregnation and handling, the average particle size of the particles A is preferably 0.1 μm or more, and more preferably 0.2 μm or more. The average particle size of the particles A is preferably 3 μm or less, more preferably 1 μm or less, even more preferably 0.5 μm or less, and particularly preferably 0.4 μm or less.

[0022] The content of particles A relative to the total mass of the aqueous dispersion is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, from the viewpoints of adhesion, bendability, and impregnation. The content of particles A relative to the total mass of the aqueous dispersion is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.

[0023] The content of particles A with respect to the total mass of the PTFE particles, particles A, and particles B is preferably 5% by mass or more, and more preferably 10% by mass or more. The content of particles A with respect to the total mass of the PTFE particles, particles A, and particles B is preferably 30% by mass or less, and more preferably 20% by mass or less.

[0024] In the aqueous dispersion of the present disclosure, the mass content of particles A is preferably equal to or greater than the mass content of particles B, from the viewpoint of the above-mentioned mechanism of action. The mass content of particles A is more preferably greater than the mass content of particles B. The mass content of particles A is further preferably equal to or greater than 1.1 times the mass content of particles B, and particularly preferably equal to or greater than 1.5 times. The mass content of particles A is further preferably equal to or less than 10 times the mass content of particles B, and particularly preferably equal to or less than 5.0 times.

[0025] From the viewpoints of adhesiveness and bendability, the melting temperature of the resin of the particles A is preferably 200° C. or higher, more preferably 260° C. or higher, and even more preferably 280° C. or higher. From the viewpoints of adhesiveness and bendability, the melting temperature of the resin of the particles A is preferably 330° C. or lower, and more preferably 320° C. or lower.

[0026] From the viewpoint of further improving the heat resistance of the composite material, the glass transition point of the particles A is preferably 50° C. or higher, and more preferably 75° C. or higher. The upper limit of the glass transition point of the particles A is not particularly limited, but is preferably 150° C. or lower, and more preferably 125° C. or lower.

[0027] As the particles A, commercially available particles can be used, or an aqueous dispersion of the particles A can be used.

[0028] <Heat melt processable fluororesin particles B having carbonyl group-containing groups> The aqueous dispersion of the present disclosure contains melt processable fluororesin particles B having a carbonyl group-containing group (ie, particles B). In the present disclosure, the "melt processible fluororesin particles B having a carbonyl group-containing group (ie, particles B)" does not include the above-mentioned "PTFE particles". The number of carbonyl-containing groups contained in the resin of particle B is 1 × 10 6 The number of particles per particle is preferably 100 to 5,000, and more preferably 100 to 3,000.

[0029] The particles B preferably contain a TFE resin having a carbonyl group-containing group as a main component, and the content thereof is preferably 100% by mass.

[0030] From the viewpoints of adhesion, bendability and impregnation, particles B are preferably particles of a resin containing TFE-based units and propylene-based units, a resin containing TFE-based units and PAVE-based units, or a resin containing TFE-based units and HFP-based units, and particles of a resin containing TFE-based units and PAVE-based units or a resin containing TFE-based units and HFP-based units are more preferred. Since the particles B have a carbonyl group-containing group, the particles B are preferably particles of a resin having a carbonyl group-containing group and containing a unit based on TFE and a unit based on PAVE (i.e., perfluoroalkoxyalkane (PFA) having a carbonyl group-containing group) or a resin having a carbonyl group-containing group and containing a unit based on TFE and a unit based on HFP (i.e., tetrafluoroethylene-hexafluoropropylene copolymer (FEP) having a carbonyl group-containing group), and more preferably PFA particles having a carbonyl group-containing group. The particles B are particularly preferably particles of a resin containing a unit based on TFE, a unit based on PAVE, and a unit based on a monomer having a carbonyl group-containing group. As the PAVE, CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE") are preferred, and PPVE is more preferred. The resin of the particles B may further contain units based on other comonomers.

[0031] From the viewpoints of adhesiveness, bendability and impregnation, the carbonyl group-containing group in the resin of particle B is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) or a carbonate group (-OC(O)O-), and more preferably an acid anhydride residue.

[0032] The carbonyl group-containing group may be contained in a unit based on a monomer in the resin of particle B, or may be contained in a terminal group of the main chain of the resin of particle B, the former being preferred. Examples of the latter embodiment include tetrafluoroethylene resins having a carbonyl group-containing group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and resins obtained by subjecting tetrafluoroethylene resins to plasma treatment or ionizing radiation treatment.

[0033] As the monomer having a carbonyl group-containing group, itaconic anhydride, complex sheet laconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH") are preferred, and NAH is more preferred from the viewpoint of excellent adhesion to the fiber substrate.

[0034] The composition ratio of each monomer unit in the resin of the particle B is not particularly limited, but for example, when the resin contains a unit based on TFE, the composition ratio of the unit based on TFE is preferably 90 to 99 mol% with respect to the total units in the resin from the viewpoint of favorably expressing the characteristics due to TFE. Furthermore, for example, when the resin contains a unit based on PAVE or a unit based on HFP, the composition ratio of the unit based on PAVE or the unit based on HFP is preferably 0.99 to 9.97 mol% with respect to the total units in the resin from the viewpoint of favorably expressing the characteristics due to PAVE or HFP. Furthermore, the composition ratio of the unit containing a carbonyl group-containing group is preferably 0.01 to 3 mol% with respect to the total units in the resin from the viewpoint of favorably expressing the characteristics due to the unit containing a carbonyl group-containing group. Specific examples of the resin of such particle B include resins described in International Publication No. 2018 / 016644.

[0035] From the viewpoint of impregnation and handling, the average particle size of the particles B is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 1 μm or more, and particularly preferably 1.5 μm or more. The average particle size of the particles B is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. Particles having the above average particle size have excellent fluidity and tend to be uniformly distributed on the surface of the fiber substrate. In addition, the particles tend to exhibit high heat resistance and electrical properties.

[0036] The content of particles B relative to the total mass of the aqueous dispersion is preferably 1% by mass or more, more preferably 2% by mass or more, from the viewpoints of adhesion, bendability, and impregnation, and is preferably 15% by mass or less, more preferably 10% by mass or less, relative to the total mass of the aqueous dispersion.

[0037] The content of particle B with respect to the total mass of the PTFE particles, particle A, and particle B is preferably 1% by mass or more, and more preferably 2% by mass or more. The content of particle B with respect to the total mass of the PTFE particles, particle A, and particle B is preferably 10% by mass or less, and more preferably 5% by mass or less.

[0038] In the aqueous dispersion of the present disclosure, the mass content of particle B is preferably less than the mass content of PTFE particles and less than the mass content of particle A from the viewpoint of impregnation. The mass content of particle B is preferably 0.01 times or more than the mass content of PTFE particles. The mass content of particle B is preferably 0.15 times or less than the mass content of PTFE particles, more preferably less than 0.10 times. The mass content of particle B is preferably 0.01 times or more than the mass content of particle A, more preferably 0.05 times or more, and even more preferably 0.1 times or more. The mass content of particle B is preferably less than 1 times the mass content of particle A, more preferably 0.5 times or less, and even more preferably 0.3 times or less.

[0039] From the viewpoints of adhesiveness and bendability, the melting temperature of the resin of particle B is preferably 200° C. or higher, more preferably 260° C. or higher, and even more preferably 280° C. or higher. From the viewpoints of adhesiveness and bendability, the melting temperature of the resin of particle B is preferably 330° C. or lower, and more preferably 320° C. or lower.

[0040] From the viewpoint of further improving the heat resistance of the composite material, the glass transition point of the particles B is preferably 50° C. or higher, and more preferably 75° C. or higher. The upper limit of the glass transition point of the particles B is not particularly limited, but is preferably 150° C. or lower, and more preferably 125° C. or lower.

[0041] Particles B may be commercially available, and as the powder of particles B, for example, EA-2000 manufactured by AGC Corporation may be used.

[0042] <Average particle diameter (D50) ratio> In the aqueous dispersion of the present disclosure, the average particle size (D50) of particles B is larger than the average particle size (D50) of particles A, and the average particle size (D50) of particles A is equal to or larger than the average particle size (D50) of PTFE particles.

[0043] From the viewpoint of impregnation, the average particle size of the particles A is at least 1 time the average particle size of the PTFE particles, and is preferably at most 2 times the average particle size of the PTFE particles. From the viewpoint of impregnation, the average particle size of the particles B is preferably at least twice the average particle size of the PTFE particles, more preferably more than twice, and even more preferably at least 4 times. The average particle size of the particles B is preferably no more than 10 times the average particle size of the PTFE particles. From the viewpoint of impregnation, the average particle size of particles B is preferably 1.5 times or more, more preferably 2 times or more, the average particle size of particles A. The average particle size of particles B is preferably 10 times or less the average particle size of particles A.

[0044] <Mass ratio of particles in aqueous dispersion> In the aqueous dispersion of the present disclosure, the total mass content of particle A and particle B is preferably less than the mass content of PTFE particles from the viewpoint of impregnation. The total mass content of particle A and particle B is preferably 0.05 times or more, more preferably 0.1 times or more, of the mass content of PTFE particles. The total mass content of particle A and particle B is preferably 0.33 times or less, more preferably 0.30 times or less, and even more preferably 0.25 times or less, of the mass content of PTFE particles.

[0045] <Other ingredients> The aqueous dispersion of the present disclosure may contain a surfactant, which can improve the dispersibility and handling properties of the aqueous dispersion. The surfactant is preferably a nonionic surfactant. The hydrophilic portion of the surfactant preferably has an oxyalkylene group or an alcoholic hydroxyl group. The hydrophobic portion of the surfactant preferably has an acetylene group, a polysiloxane group, or a fluorine-containing organic group (such as a perfluoroalkyl group). In other words, the surfactant is preferably an acetylene-based surfactant, a silicone-based surfactant, or a fluorine-based surfactant. When the aqueous dispersion contains a surfactant, the content of the surfactant relative to the total mass of the aqueous dispersion is preferably from 1 to 15% by mass.

[0046] The aqueous dispersion may contain a liquid dispersion medium. In other words, the aqueous dispersion can be regarded as an aqueous dispersion in which the PTFE particles, the particles A, and the particles B are dispersed in a liquid. In such an aqueous dispersion, the PTFE particles, the particles A, and the particles B are highly and uniformly dispersed in the liquid, so that the above-mentioned mechanism of action is easily manifested remarkably. The boiling point of the liquid dispersion medium is preferably in the range of 50 to 240° C. The liquid dispersion medium may be used alone or in combination of two or more kinds. When two or more kinds of liquid dispersion media are used, the two or more kinds of liquid dispersion media are preferably mutually compatible. Examples of liquid dispersion media include water, alcohol, N,N-dimethylformamide, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N-methyl-2-pyrrolidone, γ-butyrolactone, cyclohexanone, cyclopentanone, butyl acetate, methyl isopropyl ketone, and methyl ethyl ketone, and among these, water is preferred. The content of the liquid dispersion medium relative to the total mass of the aqueous dispersion is preferably from 30 to 95 mass %, more preferably from 35 to 90 mass %.

[0047] The aqueous dispersion may further contain a resin (hereinafter also referred to as "different resin") different from the PTFE particles, the particles A, and the particles B. The different resin may be thermosetting or thermoplastic. One type of the different resin may be used, or two or more types may be used. The different resin is not particularly limited as long as it is a resin other than PTFE particles, particles A, and particles B, and examples of the different resin include tetrafluoroethylene resins, polyester resins (such as liquid crystalline aromatic polyesters), polyimide resins, epoxy resins, maleimide resins, polyurethane resins, polyphenylene ether resins, polyphenylene oxide resins, and polyphenylene sulfide resins. When the aqueous dispersion contains a different resin, the content of the different resin relative to the total mass of the aqueous dispersion is preferably 0.1 to 5% by mass.

[0048] In addition to the above components, the aqueous dispersion may further contain other components, such as a thixotropy imparting agent, a pH adjuster, a pH buffer, a viscosity modifier, an antifoaming agent, a silane coupling agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a foaming inhibitor, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, a flame retardant, various inorganic fillers, or various organic fillers, within a range that does not impair the effects of the aqueous dispersion of the present disclosure.

[0049] The viscosity of the aqueous dispersion is more preferably 75 to 10,000 mPa·s. In this case, the aqueous dispersion has excellent dispersibility, and the handleability and homogeneity of the aqueous dispersion on the fiber substrate are easily improved. In addition, the aqueous dispersion has excellent mixability with varnishes of different resin materials. The thixotropic ratio of the aqueous dispersion is preferably 1.0 to 2.2, more preferably 1.5 to 2.0. In this case, the dispersion has excellent dispersibility and good handleability, and the uniformity of the dispersion applied to the fiber substrate is easily improved. In addition, the aqueous dispersion has excellent mixability with varnishes of different resin materials.

[0050] <Method for producing aqueous dispersion> The method for producing an aqueous dispersion of the present disclosure comprises mixing an aqueous dispersion of heat-meltable fluororesin particles A and heat-meltable fluororesin particles B having carbonyl group-containing groups, shearing the mixture to obtain a shear-treated liquid, and mixing the shear-treated liquid with an aqueous dispersion of polytetrafluoroethylene particles.

[0051] By mixing particles A and B in advance and subjecting them to shearing treatment, the uniform dispersion of each particle in the aqueous dispersion is improved. Therefore, when the aqueous dispersion is applied to the fiber substrate, each particle is uniformly applied to the fiber substrate, and a composite material having more desired properties can be obtained. Note that the stability of PTFE particles deteriorates when sheared, so it is preferable to include them in the aqueous dispersion without shearing treatment.

[0052] The aqueous dispersion of PTFE particles is preferably an aqueous dispersion of PTFE particles. As the aqueous dispersion of PTFE particles, commercially available ones can be used, for example, AD-915E manufactured by AGC. The aqueous dispersion of particles A is preferably an aqueous dispersion of particles A. As the aqueous dispersion of particles A, commercially available products can be used. Particles B may be commercially available, and an example of a powder of particle B is EA-2000 manufactured by AGC Inc. Particles B may be mixed with an aqueous dispersion of PTFE particles or an aqueous dispersion of particles A to form an aqueous dispersion of particles B, preferably an aqueous dispersion of particles B.

[0053] The above mixing may be carried out in a batch manner or a continuous manner. Examples of devices that can be used for the above mixing include stirring devices equipped with blades (Henschel mixers, pressure kneaders, Banbury mixers, planetary mixers, etc.), grinding devices equipped with media (ball mills, attritors, basket mills, sand mills, sand grinders, Dyno Mills, Dispermats, SC Mills, spike mills, agitator mills, etc.), and dispersing devices equipped with other mechanisms (microfluidizers, nanomizers, ultimizers, ultrasonic homogenizers, dissolvers, dispersers, high-speed impellers, thin film swirling type high-speed mixers, etc.). The detailed conditions for the above mixing are not particularly limited.

[0054] Examples of devices that can be used to apply the shear include a mixer, a colloid mill, and a homogenizer. The detailed conditions for the shearing are not particularly limited.

[0055] <Manufacturing method of composite materials> In the method for producing the composite material of the present disclosure, the operation of applying the aqueous dispersion of the present disclosure to the surface of a fiber substrate and heating is carried out two or more times. From the viewpoints of adhesion, bendability and impregnation, the above operation is preferably carried out three or more times, more preferably four or more times, and from the viewpoint of operability, the above operation is preferably carried out eight or less times, more preferably six or less times.

[0056] <Grant> The method of applying the aqueous dispersion of the present disclosure to a fiber substrate includes a dip coating method in which the fiber substrate is directly impregnated with the aqueous dispersion, a roller impregnation method in which the fiber substrate is directly impregnated with the aqueous dispersion and then passed through a nip roll as necessary to control the amount of the aqueous dispersion applied, a roller sizing method in which a part of a roller is impregnated with the aqueous dispersion to apply the aqueous dispersion to the roller surface, and then the fiber substrate is brought into contact with the roller to apply the aqueous dispersion, and a spray method in which the aqueous dispersion is atomized and sprayed onto the fiber substrate, etc. Among the above, the dip coating method, which is simple, is preferable. The application of the aqueous dispersion to the fibrous substrate may be carried out in a batch manner or a continuous manner, but the continuous manner is preferred from the viewpoint of easily suppressing uneven application of the aqueous dispersion to the fibrous substrate and improving productivity.

[0057] The amount of the aqueous dispersion adhered to the fiber substrate is preferably adjusted so that the amount of particle B adhered to the fiber substrate after heat treatment is 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, per 100 parts by mass of the fiber substrate.

[0058] <Heating> The heating of the aqueous dispersion applied to the fiber substrate preferably includes heating for baking the PTFE particles, the particles A, and the particles B. In addition, the heating of the aqueous dispersion applied to the fiber substrate preferably includes heating for evaporating a liquid dispersion medium that may be contained in the aqueous dispersion. The heat treatment for evaporating the liquid dispersion medium may be carried out by holding the fiber substrate to which the aqueous dispersion liquid has been applied at a temperature equal to or higher than the volatilization temperature of the liquid dispersion medium, and drying the liquid coating applied to the fiber substrate. In the heat treatment, it is not necessary to completely evaporate the liquid dispersion medium. Specifically, the amount of the liquid dispersion medium to be evaporated is preferably 50% by mass or more of the liquid dispersion medium contained in the aqueous dispersion liquid.

[0059] The heat treatment for evaporating the liquid dispersion medium may be carried out in one step at a constant temperature, or in two or more steps at different temperatures. The heating temperature is preferably 50 to 280° C. The heating time is preferably 0.1 to 30 minutes.

[0060] Examples of the heat treatment for firing include a method using an oven, a method using a ventilated drying furnace, and a method using heat rays such as infrared rays. A combination of infrared heating and hot air heating may also be used. The firing may be carried out under either normal pressure or reduced pressure, and the firing atmosphere may be any of an oxidizing gas atmosphere, a reducing gas atmosphere, and an inert gas atmosphere. The firing temperature is preferably 300 to 350° C., more preferably 310 to 340° C. The firing time is preferably 30 seconds to 30 minutes, more preferably 1 to 15 minutes. The firing temperature usually means the temperature of a dry atmosphere.

[0061] The application of the aqueous dispersion to the fiber substrate and heating can be suitably performed by using an apparatus having a dip coater and a baking furnace. The baking furnace may be a vertical baking furnace. Another example of such an apparatus is a glass cloth coating apparatus manufactured by Tabata Machinery Co., Ltd.

[0062] <Aqueous dispersion> In the method for producing a composite material of the present disclosure, the mass content of the melt processable fluororesin particles A in the aqueous dispersion used in the first operation (i.e., the operation of applying the aqueous dispersion of the present disclosure and heating) is preferably greater than the mass content of the melt processable fluororesin particles A in the aqueous dispersion used in the operations other than the first. That is, from the viewpoint of impregnation, it is preferable to set the content of particles A in the aqueous dispersion used in the first operation to be large so that particles A having a small average particle size can easily penetrate into the interior of the fiber substrate. It is preferable to decrease the content of particles A in the aqueous dispersion as the operation is repeated from the first operation to the second operation to the third operation, and accordingly increase the content of PTFE particles and the content of particles B.

[0063] In the method for producing a composite material according to the present disclosure, it is preferable to further apply an aqueous dispersion of polytetrafluoroethylene particles to the surface of the fiber substrate that has been subjected to the above-mentioned operations, and then heat the same.

[0064] In the method for producing a composite material according to the present disclosure, it is more preferable to apply an aqueous dispersion containing only polytetrafluoroethylene particles as particles to the surface of the fiber substrate that has been subjected to the above-mentioned operation, and then heat the same. That is, by forming a PTFE film on the outermost surface of the composite material, the heat resistance of the composite material is improved.

[0065] <Fiber base material> The fiber substrate used in the manufacturing method of the composite material of the present disclosure is preferably glass cloth, and more preferably glass cloth treated with a silane coupling agent to enhance affinity with the particles B. Examples of materials for the glass cloth include E glass, C glass, A glass, S glass, D glass, NE glass, L glass, and low dielectric constant glass, and E glass, S glass, and NE glass are preferred because they are easily available. Since glass cloth usually contains a sizing agent, it is preferable to reduce the amount of the sizing agent by heating before applying the aqueous dispersion to the glass cloth from the viewpoint of improving heat resistance. Examples of the sizing agent include starches such as starch, modified starch, dextrin, and amylose, synthetic polymer compounds such as carboxymethyl cellulose, polyvinyl alcohol, and acrylamide-vinyl acetate copolymer, and silane coupling agents.

[0066] The above composite materials are useful as antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, paints, cosmetics, and the like, and specifically, are useful as electric wire covering materials (aircraft electric wires, etc.), electrical insulating tapes, insulating tapes for oil drilling, materials for printed circuit boards, separation membranes (microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, and the like), electrode binders (for lithium secondary batteries and fuel cells, and the like), copy rolls, furniture, automobile dashboards, covers for home appliances, and the like, sliding members (load bearings, sliding shafts, valves, bearings, gears, cams, belt conveyors, food transport belts, and the like), tools (shovels, files, saws, and the like), boilers, hoppers, pipes, ovens, baking molds, chutes, dies, toilets, and container covering materials, and the like.

Example

[0067] One embodiment of the present disclosure will be described in detail below, but the present disclosure is not limited to these embodiments. Regarding the aqueous dispersion and the method for producing the composite material, Example 1 and Example 2 are examples, and Example 3 and Example 4 are comparative examples. Regarding the method for producing the aqueous dispersion, Example 1 is an example, and Examples 2 to 4 are comparative examples.

[0068] <PTFE particles> An aqueous dispersion (product number AD-915E manufactured by AGC) containing 60% by mass of non-thermally fusible PTFE particles (average particle diameter: 0.3 μm) <Particle A> 〔Particle A1〕Particles of a resin (melting temperature: 300 °C) containing 97.5 mol% and 2.5 mol% of units based on TFE and units based on PPVE in this order (that is, PFA particles, average particle diameter: 0.3 μm) 〔Particle A2〕Particles of a resin (melting temperature: 300 °C) containing 97.5 mol% and 2.5 mol% of units based on TFE and units based on PPVE in this order (that is, PFA particles, average particle diameter: 2.4 μm) The number of carbonyl group-containing groups contained in the resin of Particle A1 and the number of carbonyl group-containing groups contained in the resin of Particle A2 are both less than the number of carbonyl group-containing groups contained in the resin of Particle B. <Particle B> Particles (average particle diameter: 2.0 μm) composed of a resin (melting temperature: 300 °C) containing 97.9 mol%, 0.1 mol%, and 2.0 mol% of units based on TFE, units based on NAH, and units based on PPVE in this order, and having 1000 carbonyl group-containing groups per 1 × 10 6 main chain carbon atoms <Fiber substrate> Manufactured by Nitto Boseki, E-glass IPC Spec 1080

[0069] <Production of aqueous dispersion> [Aqueous Dispersion 1] The aqueous dispersion of particles A1 and the aqueous dispersion of particles B were sheared in a bead mill to obtain a sheared liquid. The sheared liquid and the aqueous dispersion of PTFE particles were then stirred and mixed to prepare aqueous dispersion 1 (the mass ratio of PTFE particles:particles A1:particles B was 8.5:1.5:0.5) containing PTFE particles, particles A1, and particles B in the order of 42.5 mass%, 7.5 mass%, and 2.5 mass%. [Aqueous Dispersion 2] An aqueous dispersion of particles A1, an aqueous dispersion of particles B, and an aqueous dispersion of PTFE particles were simultaneously sheared and mixed in a bead mill to prepare aqueous dispersion 2 containing PTFE particles, particles A1, and particles B in the order of 42.5%, 7.5%, and 2.5% by mass (the mass ratio of PTFE particles:particles A1:particles B was 8.5:1.5:0.5). [Aqueous Dispersion 3] The aqueous dispersion of particles A2 and the aqueous dispersion of particles B were sheared in a bead mill to obtain a sheared liquid. The sheared liquid and the aqueous dispersion of PTFE particles were then stirred and mixed to prepare aqueous dispersion 3 (the mass ratio of PTFE particles:particles A2:particles B was 8.5:1.5:0.5) containing PTFE particles, particles A2, and particles B in the order of 42.5 mass%, 7.5 mass%, and 2.5 mass%. [Aqueous Dispersion 4] An aqueous dispersion of particles A1 and an aqueous dispersion of PTFE particles were mixed by stirring to prepare aqueous dispersion 4 (the mass ratio of PTFE particles:particles A1 was 8.5:2) containing 42.5% by mass of PTFE particles and 10% by mass of particles A1, in that order.

[0070] <Example 1> The glass cloth was impregnated with the aqueous dispersion 1 by dip coating, passed through a drying oven at 120°C for 5 minutes, and heated and dried. After that, it was heated and baked in a far-infrared oven at 340°C for 10 minutes. The above impregnation and heating operations were repeated a total of five times. The obtained glass cloth was further impregnated with an aqueous dispersion containing 60% by mass of PTFE particles, passed through a drying oven at 120°C for 5 minutes, and heated and dried. After that, it was heated and baked in a far-infrared oven at 340°C for 10 minutes to produce a composite material.

[0071] <Example 2> A composite material was produced in the same manner as in Example 1, except that Aqueous Dispersion 2 was used as the aqueous dispersion.

[0072] <Example 3> A composite material was produced in the same manner as in Example 1, except that Aqueous Dispersion 3 was used as the aqueous dispersion.

[0073] <Example 4> A composite material was produced in the same manner as in Example 1, except that Aqueous Dispersion 4 was used as the aqueous dispersion.

[0074] <Evaluation of impregnation> The composite materials produced in Examples 1 to 4 were evaluated relatively in terms of their mass. The results are summarized in Table 1. In Table 1, A shows the composite material with the largest mass, followed by B, C, and D in decreasing order. Note that the greater the mass of the composite material, the greater the amount of resin carried, i.e., the better the impregnation ability.

[0075] <Evaluation of Adhesion> The surfaces of the composite materials produced in Examples 1 to 4 were rubbed with paper, and the mass of PTFE attached to the paper was evaluated relatively. The results are summarized in Table 1. In Table 1, A indicates the smallest mass of attached PTFE, followed by B, C, and D in order. Note that the smaller the mass of attached PTFE, the less likely the PTFE is to peel off, i.e., the better the adhesion of the PTFE in the composite material.

[0076] <Evaluation of bendability> The composite materials produced in Examples 1 to 4 were folded by hand and evaluated for the presence or absence of breakage at the folds. The results are summarized in Table 1. In Table 1, A indicates that the material was not broken at the folds, and B indicates that the material was broken at the folds. It can be said that the composite material has better bendability when it is not broken at the folds.

[0077] [Table 1]

Claims

1. An aqueous dispersion comprising polytetrafluoroethylene particles, heat-meltable fluororesin particles A, and heat-meltable fluororesin particles B having a carbonyl group-containing group, wherein the average particle size (D50) of the heat-meltable fluororesin particles A is equal to or larger than the average particle size (D50) of the polytetrafluoroethylene particles and is smaller than the average particle size (D50) of the heat-meltable fluororesin particles B having a carbonyl group-containing group.

2. 2. The aqueous dispersion according to claim 1, wherein the mass content of said melt processable fluororesin particles A is equal to or greater than the mass content of said carbonyl group-containing group-containing heat melt processable fluororesin particles B.

3. 3. The aqueous dispersion according to claim 1, wherein the total mass of the heat-meltable fluororesin particles A and the heat-meltable fluororesin particles B having a carbonyl group-containing group is less than the mass of the polytetrafluoroethylene particles.

4. 3. The aqueous dispersion according to claim 1, wherein a content by mass of the heat-meltable fluororesin particles B having a carbonyl group-containing group is less than a content by mass of the polytetrafluoroethylene particles and less than a content by mass of the heat-meltable fluororesin particles A.

5. 3. The aqueous dispersion according to claim 1, wherein the melt processable fluororesin particles A are particles of a resin containing a unit based on tetrafluoroethylene and at least one of a unit based on perfluoro(alkyl vinyl ether) and a unit based on hexafluoropropylene.

6. The aqueous dispersion according to claim 1 or 2, wherein the carbonyl-containing group is an acid anhydride residue.

7. 3. The method for producing the aqueous dispersion according to claim 1 or 2, comprising mixing an aqueous dispersion of the heat-meltable fluororesin particles A and the heat-meltable fluororesin particles B having a carbonyl group-containing group, shearing the mixture to obtain a shear-treated liquid, and mixing the shear-treated liquid with an aqueous dispersion of polytetrafluoroethylene particles.

8. A method for producing a composite material, comprising the steps of applying the aqueous dispersion according to claim 1 or 2 to a surface of a fiber substrate and heating the surface of the fiber substrate at least twice.

9. 9. The method for producing a composite material according to claim 8, wherein the content by mass of the heat-meltable fluororesin particles A in the aqueous dispersion used in the first operation is greater than the content by mass of the heat-meltable fluororesin particles A in the aqueous dispersion used in any operation other than the first operation.

10. The method for producing a composite material according to claim 8, further comprising applying an aqueous dispersion of polytetrafluoroethylene particles to the surface of the fiber substrate that has been subjected to the above-mentioned operation, and heating the same.

Citation Information

Patent Citations

  • Heat-resistant tape and its manufacturing method

    JP2020513437A

  • Powder dispersion liquid, laminate, film, and impregnated woven fabric

    WO2020004339A1